Greater pain and functional impairment in chronic erosive hand osteoarthritis compared to treated rheumatoid arthritis: A comparative study - S. Berkani; S. Tuffet; A. Rousseau; N. Rincheval; E. Maheu; B. Combes; A. Saraux; B. Fautrel; L. Gossec; F. Berenbaum; J. Sellam; A. Courties (Osteoarthritis and Cartilage Open)
Objectives: To compare the burden of established chronic rheumatoid arthritis (RA) and erosive hand osteoarthritis (EHOA), in terms of pain, functional impairment, comorbidities, and cardiometabolic diseases (CMD). Methods: This study included EHOA patients from the inclusion visit of the DIGICOD cohort and RA patients from the 10th year visit of the ESPOIR cohort. Outcomes were pain intensity (≥40 on a 0–100 ​mm visual analog scale [VAS]), VAS fatigue, and functional impairment, measured by normalized (0–100) Health Assessment Questionnaire (HAQ) for RA and the AUStralian CANadian Osteoarthritis Hand (AUSCAN) function for EHOA and binarized by their medians. Comorbidities and CMD were also assessed. Logistic regression models adjusted for age, sex, body mass index, and socio-educational level were used to compare outcomes. Results: We included 138 EHOA and 379 RA patients. EHOA patients were older (median age 67.3 vs. 48.6 years, p ​< ​0.001). EHOA patients were more likely to experience higher pain at mobilization (OR ​= ​3.13 95 ​% CI [1.74 to 5.68]) and greater functional impairment (OR ​= ​2.27, 95 ​% CI [1.26 to 4.17]) than RA patients. There was no difference for fatigue and pain at rest. The overall risk of comorbidities was lower in EHOA patients in multivariate analysis (OR ​= ​0.25, 95%CI [0.13–0.48]). There was no significant difference in CMD risk. Conclusion: After more than 10 years of disease duration, EHOA is associated with greater pain and functional impairment than treated RA but with fewer comorbidities. This highlights the significant unmet need for effective therapies for EHOA patients.